2009
DOI: 10.1002/ddr.20316
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a biodegradable dental chip containing chlorhexidine in chitosan base as a targeted drug delivery in the management of chronic periodontitis in patients

Abstract: Chlorhexidine is one of the commonly used agents in the treatment of periodontitis. In the present study, a biodegradable dental chip of chitosan containing chlorhexidine was evaluated both in vitro and in vivo, as a targeted drug delivery system in patients of chronic periodontitis. Thirty patients having localized periodontal pockets Z5 mm were selected. At baseline, the experimental patients received full mouth scaling and root planing followed by placement of a chlorhexidine chip. The placebo group receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…These studies reported mean PD decreases of 0.84 mm and 0.80 mm, respectively. Our results are also in agreement with studies performed by [6,15,24] using periodontal chips containing chlorhexidine as local delivery agents in the management of chronic periodontitis. These previous studies demonstrated that when a biodegradable chlorhexidine chip is used as an adjunct to conventional periodontal therapy critical enhancements are obtained in periodontal probing depths and attachment levels compared to the use of scaling and root planning alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These studies reported mean PD decreases of 0.84 mm and 0.80 mm, respectively. Our results are also in agreement with studies performed by [6,15,24] using periodontal chips containing chlorhexidine as local delivery agents in the management of chronic periodontitis. These previous studies demonstrated that when a biodegradable chlorhexidine chip is used as an adjunct to conventional periodontal therapy critical enhancements are obtained in periodontal probing depths and attachment levels compared to the use of scaling and root planning alone.…”
Section: Discussionsupporting
confidence: 92%
“…After drying overnight at room temperature, the resultant film was cut into small rectangular chips 0.5 × 0.5 sq⋅cm in size and 0.16 ± 0.02 mm thick. These chips were then covered in aluminum foil and kept in sterile vials at room temperature [15].…”
Section: Preparation Of the Biodegradable Chitosan Chipmentioning
confidence: 99%
“…Clinically, chitosan also has high potential in dental applications, and it has used to repair socket after dental extraction (Ezoddini-Ardakani, 2011). Other research also reported that biodegradable dental chip containing chlorhexidine or thymoquinone was applied for management of chronic periodontitis in patients (Al-Bayaty et al, 2013; Jothi et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial agents are commonly used for various dental procedure such as endodontic 41,42 and periodontic treatments 43,44 . The use of BG can increase the pH of the aqueous solution and generate antimicrobial effects.…”
Section: Antimicrobial Agent and Disinfectantmentioning
confidence: 99%